Increasing Predominance of Norovirus GII.17 over GII.4, United States, 2022–2025 - Leslie Barclay; Jan Vinjé (Emerging Infectious Diseases)
Norovirus GII.17 outbreaks in the United States increased from <10% during the 2022–23 season to 75% during the 2024–25 season, surpassing the number of GII.4 outbreaks. The norovirus season also started earlier in 2024–25 than in previous seasons. Continued norovirus surveillance is needed to detect and monitor emerging strains.